Manhattan Area Habitat for Humanity’s Women Build Project – Rebuilding a community one person and one home at a time. - Hathaway, Alec (My University, 2019)
In May 2019, the Morse Family Scholarship aided me in spearheading Manhattans first-ever Women Build – a community-inclusive event designed to garner community support, specifically women, for the restoration of Habitat homes throughout the Manhattan area. Sixty women volunteers gathered over four days across Manhattan to partake in Women Build restoration activities. This project was mutually beneficial for the Manhattan community and organization due to the lack of women volunteers on Habitats construction sites. This lapse comes from women not feeling comfortable taking on male-dominated roles. Statistically speaking, women only constitute 9% of all construction-related jobs and projects within the United States (Women in the labor force: a databook, 2018). We wanted the Women Build project to help women in our community feel more comfortable with their hands-on abilities by breaking the stigma that women are incapable of occupying spaces in male-dominated roles. The Women Build project was also a great catalyst to disseminate information and raise awareness about Manhattan Area Habitat for Humanity’s mission and purpose within this community.